The Art of Continuous Change: Linking Complexity Theory and Time-Paced Evolution in Relentlessly Shifting Organizations - Brown, Shona L.; Eisenhardt, Kathleen M. (Administrative Science Quarterly, 1997)
Shona L. Brown, Kathleen M. Eisenhardt, The Art of Continuous Change: Linking Complexity Theory and Time-Paced Evolution in Relentlessly Shifting Organizations, Administrative Science Quarterly, Vol. 42, No. 1 (Mar., 1997), pp. 1-34